217k views
3 votes
Which choices are equivalent to the expression below? Check all that apply.A.B.C.6iD.-6

Which choices are equivalent to the expression below? Check all that apply.A.B.C.6iD-example-1

1 Answer

4 votes

The expression is given to be:


√(-36)

Apply the radical rule:


√(-a)=√(-1)√(a)

Therefore, the expression becomes:


√(-36)=√(-1)√(36)

Recall the imaginary number rule:


√(-1)=i

Therefore, the expression becomes:


=i√(36)

Simplify:


=6i

The correct option is OPTION C.

User Ordonezalex
by
7.4k points